Accounting and the Virtues of Anarchy - Warwick Funnell (Australasian Accounting, Business and Finance Journal, 2007)
The ability of accounting to be used for the purposes of economic, social and political oppression is now well recognised in the critical accounting literature. Accounting is far more than an innocuous technology of rational calculation and accountability upon which management and the efficient operation of markets depend. Its contributions to maintaining the hegemony of the state are primarily through its close association with the protection and promotion of property rights. For the anarchist this relationship is the source of entrenched injustice which alienates individuals from their fundamental, moral nature. Elimination of the state allows justice to be reasserted and society to operate on moral principles. When the very existence of the state is questioned, as does anarchism, understanding of the fundamental nature and contributions of accounting need to be renegotiated.
Keywords: anarchism; state; property; entitlement; justice